2009
DOI: 10.1159/000227771
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Radiotherapy Has No Value for Patients with T2–3, N0 Adenocarcinomas of the Rectum

Abstract: Background: Treatment of rectal cancer with preoperative radiotherapy followed by total mesorectal excision is nowadays the standard treatment. It reduces local recurrences and improves overall survival. However, in patients with T2–3, N0 rectal cancer, the role of preoperative radiotherapy remains controversial. The aim of this study was to review the benefit of radiotherapy in T2 and T3, N0 rectal cancer patients. Methods: Between 1996 and 2003, 103 patients with T2–3, N0 rectal cancer were identified in our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
0
4
0
1
Order By: Relevance
“…Researchers suggested it should be not necessary to perform neoadjuvant or adjuvant radiotherapy on CRM negative cases according to preoperative evaluation. Ferenschild et al [ 36 ] found that T2–3N0 patients did not benefit from neoadjuvant radiotherapy (local recurrence rate: 6% vs 6% P > 0.05). Taylor et al [ 37 ] reported 5-year local recurrence rate was only 3% for T2/T3a/T3b and CRM negative patients without neoadjuvant radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers suggested it should be not necessary to perform neoadjuvant or adjuvant radiotherapy on CRM negative cases according to preoperative evaluation. Ferenschild et al [ 36 ] found that T2–3N0 patients did not benefit from neoadjuvant radiotherapy (local recurrence rate: 6% vs 6% P > 0.05). Taylor et al [ 37 ] reported 5-year local recurrence rate was only 3% for T2/T3a/T3b and CRM negative patients without neoadjuvant radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports suggest that the effect of (neo)adjuvant therapy depends on factors such as TNM stage, tumour position, surgical technique, biological behaviour as well as on patient characteristics [10][11][12][13][14]. A more personalized approach, tailored to these factors, might improve the balance between beneficial and adverse effects of (neo)adjuvant treatment and allow better patient selection.…”
mentioning
confidence: 99%
“…Since neoadjuvant CRT only reduces risk of local recurrence but not distant metastases [ 10 ], and inevitably results in short-term and long-term toxicities [ 11 ], some studies questioned the strategy of routine application of neoadjuvant CRT to patients with T3N0 rectal cancer, and proposed that only those at high risk of local recurrence should be treated with neoadjuvant CRT [ 2 , 12 ].…”
Section: Introductionmentioning
confidence: 99%